1979
DOI: 10.1111/j.1471-6402.1979.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Social Implications of Sex-Choice Technology

Abstract: A survey of 710 undergraduates was conducted to assess the probable patterns of utilization of sex-choice technology when it becomes widely available. Ideal family composition was determined along with demographic and attitudinal variables. Results confirmed the overwhelming preference for male children, in general, and male firstborn children, in particular: 85% wanted a firstborn boy, while 73% wanted a secondborn girl. Reasons for the choice reflected both considerable knowledge of advantages accruing to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Various researchers have supported this position. Fidell et al (1979) found that 73 per cent of their sample would select a girl second, which supported Markle and Nam's (1971) finding of 60 per cent second-born girl preference. The present study was an initial effort to assess second-born preference among potential users of sex selection technology.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Various researchers have supported this position. Fidell et al (1979) found that 73 per cent of their sample would select a girl second, which supported Markle and Nam's (1971) finding of 60 per cent second-born girl preference. The present study was an initial effort to assess second-born preference among potential users of sex selection technology.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have explored the willingness of respondents to use sex selection technology to translate son preference into reality (Fidell et al, 1979;Gilroy and Steinbacher, 1983;Markle and Nam, 1971;Pebley and Westoff, 1983;Steinbacher and Gilroy, 1990). Results indicate that potential users have as strong and, in some instances, a stronger first-born sex preference than the general population.…”
Section: Sex Selection Technology Utilization: Further Implications Fmentioning
confidence: 87%
See 2 more Smart Citations
“…(Westoff & Rindfuss, 1974). In other social science journals, the existence of technology that controls for sex at the time of conception is repeatedly referred to as sex choice and the ability of individuals to choose the sex of their offspring (Fidell, Hoffman, & Keith-Spiegel, 1979;Gilroy & Steinbacher, 1983;Steinbacher & Gilroy, 1989). The vocabulary of "choice" also makes its way into technical discussions that have as their audience policy analysts (Wiegle, 1985), foreshadowing the depiction of sex selection technology that will dominate public debate and discussion.…”
Section: From Sex Control To Sex Choicementioning
confidence: 99%